2021
DOI: 10.3389/fneur.2021.615593
|View full text |Cite
|
Sign up to set email alerts
|

The Survival Benefit of Postoperative Bacterial Infections in Patients With Glioblastoma Multiforme: Myth or Reality?

Abstract: Glioblastoma multiforme (GBM), the most common malignant brain tumor, universally carries a poor prognosis. Despite aggressive multimodality treatment, the median survival is ~18–20 months, depending on molecular subgroups. A long history of observations suggests antitumor effects of bacterial infections against malignant tumors. The present review summarizes and critically analyzes the clinical data providing evidence for or against the survival benefit of post-operative bacterial infections in GBM patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…One of the potential activators of the immune response may also be a bacterial infection. It was found that bacterial-based tumor therapy inhibits tumor cell growth in different cancer types, like sarcomas or superficial bladder cancer (5,6). Here we present two case reports of unexpectedly long survival in patients with chronic and prolonged bacterial infection at the site of craniotomy after standard therapy of HGG.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…One of the potential activators of the immune response may also be a bacterial infection. It was found that bacterial-based tumor therapy inhibits tumor cell growth in different cancer types, like sarcomas or superficial bladder cancer (5,6). Here we present two case reports of unexpectedly long survival in patients with chronic and prolonged bacterial infection at the site of craniotomy after standard therapy of HGG.…”
mentioning
confidence: 78%
“…Another proposed mechanism is the stimulation patient's immune response within or near the tumor bed while avoiding the systemic response (6,11). It is well known that GBM induces tumor-associated immune suppression both within its microenvironment as well as systematically (20).…”
Section: Immune Suppression In Gbmmentioning
confidence: 99%
See 1 more Smart Citation
“…In brain tumors, SSIs have been reported to occur in 4–8% of the surgeries (Scheer et al 2023 ; Uzuka et al 2017 ). For a long time, it has been hypothesized that bacterial SSIs might positively affect survival time in cancer patients (Kazim et al 2021 ; Nauts 1989 ). In the late nineteenth and early twentieth century, the orthopedic surgeon and cancer researcher William B. Coley even inoculated bacterial organisms (Coley's toxins) into more than 1000 patients with inoperable cancer and reported an “anti-cancer effect” of bacterial infections (Coley 1898 , 1991 ; McCarthy 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…In pancreatic cancer, and in contrast to normal pancreatic tissue, bacteria and fungi colonize the cancerous tissues, affecting the response and prognosis to treatment [ 15 ]. Interestingly, bacterial infection within or near the tumor bed has also been suggested to stimulate patients’ immune responses in brain tumors, for example, in glioblastoma (GBM) patients [ 16 ].…”
Section: Introductionmentioning
confidence: 99%